Dukungan Sosial dan Resiliensi Pada Remaja Pasca Kematian Orang Tua: Sebuah Kajian Literatur - Calsum, Astri Yani; Purwandari, Eny (Universitas Al Azhar Indonesia, 2024)
Losing a parent due to death is a meaningful event and has a profound impact on adolescents. It often creates a sense of sadness, loss and ongoing trauma. The role of parents is very important in supporting the developmental stages of adolescents. This study uses the Systematic Literature Review (SLR) approach to evaluate the influence and relationship between social support and resilience in adolescents after the death of a parent. The data for analysis is obtained through Google Scholar, accessed through Publish or Perish (Pop) using the keywords